Proximate, Antioxidant, Vitamins, and Total Phenolic Composition of Piper guineense Seeds As Affected by Soaking and Air-Resting - Attaugwu, Roseline Nwabugo; Anyadioha, Josephat Ikechukwu; Maxwell, Kosisochukwu Precious (Indonesian Association of Food Technologists, 2025)
This study investigated the effects of soaking and air-resting on the proximate, antioxidant vitamin and total phenol content, and antioxidant activities of Piper guineense seeds. The seed extracts were prepared by soaking the seeds in water for four hours, air-resting for 30, 60, 90, and 120 minutes, and re-soaking for another four hours before being milled and extracted. Proximate composition showed that protein ranged from 4.29-7.30%, moisture content (21.90-62.35%), fat (6.93-8.05%), ash (1.75-7.61%), crude fiber (13.77-38.34%), and carbohydrate (3.39-6.83%). Vitamin A, vitamin C, and vitamin E results ranged from 329.05-908.14 IU, 64.92-95.38 mg/100 g, and 3.7-7.5 mg/100 g. The ferric reducing power of the seed extracts ranged from 66.54 mg/100 g-116 mg/100 g, TAC ranged from 2.50-38.08 mg/ml, antioxidant activity with DPPH ranged from 55.76-66.12% at 50 mg/ml, 68.18-80.44% at 75 mg/ml, 74.79-88.43 % at 100 mg/ml. The results showed a loss of carbohydrates, fats, vitamin C, and total phenols. The results for the 30-minute treatment showed minimal nutrient losses and highest antioxidant activities compared to 60, 90, and 120 minutes, respectively. Therefore, the antioxidants of soaked and air-rested Piper guineense seed extracts can help reduce free radicals that cause oxidative stress, leading to degenerative diseases.